JUMAT AGUNG: PERAYAAN AMBIGU ANTARA LITURGI DAN KESALEHAN UMAT? - Ritan, Timoteus Enga (UNIKA Santo Thomas, 2016)
Liturgy and Popular Piety flourish and growing in the life of the faithful. The relationship between them evolving and affect each other. Liturgy are in a higher level when compared with the Popular Piety. However, in the practice often equated Liturgy, and even under the domination of the Popular Piety. Different meaning, mutually influential. Therefore, the most important thing here that we know the meaning correctly, so there is no deviation. An ambiguous celebration celebrated, because it is influenced by a variety of domination popular piety. The most important thing is shown that the extent to which the Popular Piety affected also to supports the Liturgy or the Liturgy itself can develop its own without the Popular Piety. Good Friday are in two rhythm between Liturgy and popular piety. Good Friday is a part of the celebration of Easter, which is celebrated differently. Look different, but it has a deep meaning in the journey towards Easter of Christ.